STEAM IN BIOLOGY LESSONS USE OF TECHNOLOGIES - Tillayeva, Zebo Yorbekovna (Confrencea, 2023)
Using red cabbage leaves, you can determine the pH of the environment. The method of paper chromatography is used to study pigments in plants.